A Low-Carbohydrate Diet Realizes Medication Withdrawal: A Possible Opportunity for Effective Glycemic Control - Han, Yuxin; Cheng, Bingfei; Guo, Yanjun; Wang, Qing; Yang, Nailong; Lin, Peng (Frontiers in Endocrinology, 2021)
Objective: Multiple studies have confirmed that diet restrictions can effectively realize glycemic control and reduce metabolic risks in patients with type 2 diabetes mellitus (T2DM). In 2018, the American Diabetes Association (ADA) and European Association for the Study of Diabetes (EASD) stated that individuals can select a low-carbohydrate diet (LCD) according to their needs and preferences. Owing to the influence of Chinese traditional eating habits, only a small portion of patients in China have achieved their blood glucose goals. As a result, the Chinese government will incur huge expenditures. Method: This study recruited 134 T2DM participants and randomly assigned them to the LCD group (n = 67) or the low-fat diet (LFD) group (n = 67). All of the patients had a fixed amount of exercise and were guided by clinicians. After a period of dietary washout, all of the patients received corresponding dietary education according to group. The follow-up time was 6 months. The indicators for anthropometry, glycemic control and medication application parameters were collected and compared between the two groups. Results: There were 121 participants who finally entered the study. The proportions of calories from three major nutrients the participants consumed met the requirements of LCD and LFD. Compared with baseline, the pre-post differences of body weight, BMI and several other indicators were significant except for dosages of insulin used in the LCD group and MES in the LFD group. After the intervention, body weight, body weight index (BMI), fasting blood glucose (FBG), postprandial 2-h blood glucose (PPG), and glycosylated hemoglobin (HbA1c) levels in the LCD group decreased significantly (p < 0.05) compared to the LFD group. The number of patients using lipid-lowering agents was significant higher in LCD group and lower in LFD group. However, there was no significant difference between the two groups for antihypertensive, hormone-replacement and other agents. Conclusions: The LCD diet can decrease body weight, glycemic levels, MES and lipid-lowering agents more than the LFD diet, thus decreasing cost burden in Chinese patients with T2DM. Strict diet control and monitoring are the keys to managing diabetes.